Ideological Complex Systems: Mathematical Theory. Issue 2 (18th July 2014) - Nescolarde‐Selva, Josué Antonio; Usó-Doménech, José Luis; Lloret‐Climent, Miguel
Abstract : The goal of this article is to build an abstract mathematical theory rather than a computational one of the process of transmission of ideology. The basis of much of the argument is Patten's Environment Theory that characterizes a system with its double environment (input or stimulus and output or response) and the existing interactions among them. Ideological processes are semiotic processes, and if in Patten's theory, the two environments are physical, in this theory ideological processes are physical and semiotic, as are stimulus and response. © 2014 Wiley Periodicals, Inc. Complexity 21: 47–65, 2015